2017
DOI: 10.1155/2017/4368659
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Toxocariasis among Patients Clinically Suspected to Have Visceral Toxocariasis: A Retrospective Descriptive Study in Sri Lanka

Abstract: Introduction Human toxocariasis is caused by several species of the nematode Toxocara. Two common clinical syndromes are ocular and visceral larva migrans. Objectives To determine the Toxocara antibody positivity in clinically suspected VLM patients and to describe demographic factors and clinical manifestations of seropositive patients. Methods 522 clinically suspected patients were studied between 1993 and 2014. Relevant data was gathered from referral letters. Serum samples were subjected to Toxocara antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…For HT, Gillespie et al [26] reported eosinophilia > 0.4 × 10 9 /l in 28 patients with VLM; of these, 19 scored positive in TES antigen detection using a sandwich ELISA with the monoclonal Ab Tcn-2. In addition, the association between seropositivity (by TES-Ab ELISA) and eosinophilia has been extensively documented [1,10,13,14,[29][30][31][32][33]. These data are in line with our findings.…”
Section: Active Ht Is Associated With Eosinophiliasupporting
confidence: 92%
“…For HT, Gillespie et al [26] reported eosinophilia > 0.4 × 10 9 /l in 28 patients with VLM; of these, 19 scored positive in TES antigen detection using a sandwich ELISA with the monoclonal Ab Tcn-2. In addition, the association between seropositivity (by TES-Ab ELISA) and eosinophilia has been extensively documented [1,10,13,14,[29][30][31][32][33]. These data are in line with our findings.…”
Section: Active Ht Is Associated With Eosinophiliasupporting
confidence: 92%
“…After hatching eggs in the small intestine of the human, the infective larvae (L3) migrate to different tissues (especially liver, lungs, brain, and eyes) by blood circulation and cause two main syndromes: visceral and ocular, and less commonly neurological larva migrans syndrome. Human toxocariasis in most cases is asymptomatic, which is called covert toxocariasis [3]. Seroprevalence studies show a relatively high prevalence of human toxocariasis in different parts of the world [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a relationship between the level of anti- Toxocara antibodies and eosinophilia or IgE concentration in the current study was consistent with some previous findings. Studies in Iran, Sri Lanka and Brazil did not document a statistically significant correlation between eosinophilia and Toxocara seropositivity ( 3 , 41 , 42 ). A little correlation between lgG and lgE in the sera of patients with symptomatic toxocariasis was reported ( 43 ).…”
Section: Discussionmentioning
confidence: 85%
“…Sampling tissue biopsies or fluid samples can be extremely difficult, so a diagnosis of human toxocariasis has mostly relied on the use of immunological techniques. Enzyme-linked immunosorbent assay (ELISA) based on Toxocara excretory-secretory (TES) antigens from infective-stage larvae have been widely used for serodiagnosis of human toxocariasis ( 2 , 3 ). However, immunodiagnostic tests are not capable of distinguishing between current and past infection so some other tests have been used to support the diagnosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%